Relevant interrelationships between science and mass communication - Kosiuk,Oksana (ACCESS Press Publishing house, 2021)
In the context of pandemic media audience focus their attention on scientific information. Therefore, studying this issue, we aimed to analyze modern mass communication activities as a historical phenomenon and compare it with scientific. With this objective we have researched database sources, explored web-sites of foreign and Ukrainian media, compared their subject areas, identified ways of communicating and covering scientific information, compared genre opportunities and considered the Covid-19 pandemic on a larger media-scientific scale. It has been defined that mass communication in its basic parameters is almost literal equivalent of popular level of scientific activity, so its problems and achievements are also associated with rational solution of global crises of civilization and culture.
Keywords: communication; semiotics